2010
DOI: 10.1159/000320185
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anti-Quorum-Sensing Activity of Edible Plants and Fruits through Inhibition of the N-Acyl-Homoserine Lactone System in <i>Chromobacterium violaceum</i> and <i>Pseudomonas aeruginosa</i>

Abstract: Background: To find out an alternative strategy to antibiotic usage against bacterial infection. Materials and Methods: The purpose of this study is to describe the quorum-sensing (QS) inhibitory activity of edible plants and fruits against N-acyl-homoserine lactone (AHL)-mediated violacein production in Chromobacterium violaceum and virulence factor expression in Pseudomonas aeruginosa PAO1. Results: Aqueous extracts of Ananas comosus (Bromeliaceae), Musa paradiciaca (Musaceae), Manilkara zapota (Sapotaceae) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
85
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(96 citation statements)
references
References 35 publications
10
85
1
Order By: Relevance
“…Several potential QS inhibitor compounds have been discovered from eukaryotic and prokaryotic origin, which includes metabolites like halogenated furanones from Australian macroalgae Delisea pulchra [14], AHL degrading enzymes such as lactonase from Bacillus sp. [7], lactonase and acylase from actinobacteria, a, b and c proteobacteria [9] and other unknown compounds from edible plants and fruits [16], garlic [5], Laminaria digitata [3], Ahnfeltiopsis flabelliformis [12], Coral associated bacterial extracts [27] and Bacillus sp. SS4 [17] that are known to interfere with AHL molecules mediated QS.…”
Section: Discussionmentioning
confidence: 99%
“…Several potential QS inhibitor compounds have been discovered from eukaryotic and prokaryotic origin, which includes metabolites like halogenated furanones from Australian macroalgae Delisea pulchra [14], AHL degrading enzymes such as lactonase from Bacillus sp. [7], lactonase and acylase from actinobacteria, a, b and c proteobacteria [9] and other unknown compounds from edible plants and fruits [16], garlic [5], Laminaria digitata [3], Ahnfeltiopsis flabelliformis [12], Coral associated bacterial extracts [27] and Bacillus sp. SS4 [17] that are known to interfere with AHL molecules mediated QS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, EA extract (100 µg/ml) has shown a maximum of 37.1±1.4% inhibition against violacein pigment production. It was reported that Cuminum cyminum methanol extract (500 µg/ml) has exhibited nearly 30% inhibition of violacein production [32]. Remarkably, 100 µg/ml of EA extract of LAB38 was sufficient to show 37% inhibition of violacein production.…”
Section: Inhibition Of Qs-regulated Pigment Productionmentioning
confidence: 94%
“…Musthafa, Ravi, Annapoorani, Packiavathy, and Pandian (2010) demonstrated that the aqueous extract of pineapple (Ananas comosus) and sapodilla (Manilkara zapota) fruits were able to inhibit the AHL system in C. violaceum CV026 as well as in P. aeruginosa PAO1, affecting violacein and pyocyanin pigment production, staphylolytic protease, elastase production and biofilm formation, respectively. Apricot (Prunus armeniaca) also showed anti-QS activity against the biosensor strains C. violaceum CV026 and P. aeruginosa PAO1 inhibiting violacein production and swarming motility, respectively (Koh & Tham, 2011).…”
Section: Fruitsmentioning
confidence: 99%
“…Jakobsen, Bragason, et al (2012) have also described a QS-inhibitory activity in the biosensor QSIS1 for thyme and rosemary extracts as well as for chervil and lemon grass extracts. Ocimum sanctum leaf extract, also known as holy basil, laurel (Laurus nobilis) and two pepper species (P. nigrum and P. longum) also exhibited anti-QS activity against a biosensor strain (C. violaceum) (Al-Hussaini & Mahasneh, 2009;Musthafa et al, 2010;Tan et al, 2013). When tested against the opportunistic pathogen P. aeruginosa PAO1, holy basil also decreased total proteolytic activity and LasB elastase activity (Musthafa et al, 2010).…”
Section: Fresh Herbs and Spicesmentioning
confidence: 99%